2021
DOI: 10.1371/journal.pone.0257616
|View full text |Cite
|
Sign up to set email alerts
|

Four new species of Russula subsection Roseinae from tropical montane forests in western Panama

Abstract: Species of the genus Russula are key components of ectomycorrhizal ecosystems worldwide. Nevertheless, their diversity in the tropics is still poorly known. This study aims to contribute to the knowledge of the diversity of Russula species classified in subsection Roseinae based on specimens recently collected in tropical montane rainforests in western Panama. A five gene multilocus phylogeny based on the nuclear markers ITS nrDNA, MCM7, RPB1, RPB2 and TEF-1α was constructed to identify the systematic position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, a tropical African origin has long been posited for Russulaceae based on endemism and morphological distinctiveness (Pirozynski, 1983; Buyck et al ., 1996). In the wider Neotropics, Russulaceae occur in all highland and lowland regions where ECM vegetation is found, and modern work has revealed a plethora of new species (Buyck & Ovrebo, 2002; Miller et al ., 2002, 2012; Wartchow & Cavalcanti, 2010; Cheype & Campo, 2012; Sà et al ., 2013, 2019; Sà & Wartchow, 2013, 2016; Wartchow et al ., 2013; Montoya et al ., 2014; Trierveiler‐Pereira et al ., 2014; Crous et al ., 2017; Delgat et al ., 2020; Duque Barbosa et al ., 2020; Silva‐Filho et al ., 2020; Manz et al ., 2021; Vera et al ., 2021). Several lowland neotropical Russulaceae have affinities with tropical African species (Buyck, 1990; Buyck & Ovrebo, 2002; De Crop et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, a tropical African origin has long been posited for Russulaceae based on endemism and morphological distinctiveness (Pirozynski, 1983; Buyck et al ., 1996). In the wider Neotropics, Russulaceae occur in all highland and lowland regions where ECM vegetation is found, and modern work has revealed a plethora of new species (Buyck & Ovrebo, 2002; Miller et al ., 2002, 2012; Wartchow & Cavalcanti, 2010; Cheype & Campo, 2012; Sà et al ., 2013, 2019; Sà & Wartchow, 2013, 2016; Wartchow et al ., 2013; Montoya et al ., 2014; Trierveiler‐Pereira et al ., 2014; Crous et al ., 2017; Delgat et al ., 2020; Duque Barbosa et al ., 2020; Silva‐Filho et al ., 2020; Manz et al ., 2021; Vera et al ., 2021). Several lowland neotropical Russulaceae have affinities with tropical African species (Buyck, 1990; Buyck & Ovrebo, 2002; De Crop et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that ectomycorrhizal fungi, wood-decaying fungi, soil saprotrophs, and litter saprotrophs were predominantly present in mixed forests ( Figure 4 b). Ectomycorrhizal fungi, such as Lactarius [ 46 , 47 ], Amanita [ 48 , 49 ], Russula [ 50 , 51 ], and Cortinarius [ 52 , 53 ], are known to associate primarily with Quercus and Pinus trees. Since mixed forests in our study area consist of Quercus mongolica and Pinus koraiensis , it is likely that the presence of these tree species contributes to the higher abundance of ectomycorrhizal fungal species.…”
Section: Discussionmentioning
confidence: 99%